Energy and exergy analysis of air based photovoltaic thermal (PVT) collector: a review - Ahmad Fudholi; Mariyam Fazleena Musthafa; Abrar Ridwan; Rado Yendra; Ari Pani Desvina; Rahmadeni Rahmadeni; Tri Suyono; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2019)
Photovoltaic thermal (PVT) collectors convert solar radiation directly to both electrical and thermal energies. A PVT collector basiccaly combines the functions of a flat plate solar collector and those of a PV panel. This review presents thermodinamics fundamentals, descriptions, and previous works conducted on energy and exergy analysis of air based PVT collector. Studies in 2010 to 2018 of the energy and exergy analysis of air based PVT collectors are summarized. The energy and exergy efficiency of air based PVT collector ranges from 31% to 94% and 8.7% to 18%, respectively. In addition, flat plate solar collector is presented. Studies conducted on air based PVT collectors are reviewed.